Clinical and demographic characteristics associated with postural instability in patients with schizophrenia - Koreki, Akihiro; Tsunoda, Kenichi; Suzuki, Takefumi; Hirano, Jinichi; Watanabe, Koichiro; Kashima, Haruo; Uchida, Hiroyuki (Journal of clinical psychopharmacology, 2011)
As people with schizophrenia grow older, prevention of falls in this older population has become a public health priority. It is therefore critically important to identify risk factors to effectively prevent falls. For this purpose, the degree of postural sway can serve as a convenient index of risk assessment. The objective of this study was to find clinical and demographic characteristics associated with postural instability. Inpatients and outpatients with schizophrenia or related psychosis were recruited at 2 hospitals in Japan. The clinical stabilometric platform, which measured a range of the trunk motion, and extrapyramidal side effects were evaluated between 9 and 11 A.M. Four hundred two subjects were enrolled (age: mean, 55.5 [SD, 14.4] years). A univariate general linear model showed that the use of antipsychotic drugs with a chlorpromazine equivalent of 10 or greater, being overweight, and inpatient treatment setting were associated with a greater degree of the range of postural sway. Another general linear model, including a subgroup of 300 subjects who did not present any extrapyramidal side effects, not only consolidated these findings, but also revealed a great degree of postural sway in older subjects. In addition, quetiapine was found to be associated with a greater range of postural sway among atypical antipsychotics. Schizophrenia patients generally showed a greater degree of postural instability, compared with the reference data of healthy people. These findings highlight truncal instability as a risk factor of falls in patients with schizophrenia, especially when they are overweight, old, and/or receiving antipsychotics with a chlorpromazine equivalent of 10 or greater, including quetiapine.